The Role of Social Media in Sustainable Branding - Santos, Sara (2024)
Consumers increasingly expect brands to make a positive impact on communities and societies. Nowadays, communicating about corporate social responsibility can involve storytelling techniques, making the issues more understandable and relatable than straightforward and logical messages. However, in the academic field, research needs to gather and systematise the relationship between these topics and their influence on stakeholders' attitudes. This chapter aims to understand how stakeholders act towards storytelling content related to corporate social responsibility on social media. Thirteen academic papers were gathered from the Scopus and Web of Science databases, which were in English and openly accessible, fulfilling the inclusion criteria. These papers provided insights into stakeholders' perspectives on corporate social responsibility storytelling on social media. This study holds significant implications for businesses, emphasising the value of crafting narratives on social media.